2019
DOI: 10.1371/journal.pbio.3000398
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Toll-like receptor 7/8 encoded by the X chromosome alters sperm motility and provides a novel simple technology for sexing sperm

Abstract: In most mammals, the male to female sex ratio of offspring is about 50% because half of the sperm contain either the Y chromosome or X chromosome. In mice, the Y chromosome encodes fewer than 700 genes, whereas the X chromosome encodes over 3,000 genes. Although overall gene expression is lower in sperm than in somatic cells, transcription is activated selectively in round spermatids. By regulating the expression of specific genes, we hypothesized that the X chromosome might exert functional differences in spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 52 publications
7
71
0
Order By: Relevance
“…If dosage compensation was significantly affected by the autosomal SD system, then a strong male-specific viability defect would be expected, but the autosomal SD system does not cause a strong sex bias (Denell et al, 1969). Recently, meiotic drive has also been used to sex select mouse embryos, but this system has not yet been used to study dosage compensation (Umehara et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…If dosage compensation was significantly affected by the autosomal SD system, then a strong male-specific viability defect would be expected, but the autosomal SD system does not cause a strong sex bias (Denell et al, 1969). Recently, meiotic drive has also been used to sex select mouse embryos, but this system has not yet been used to study dosage compensation (Umehara et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Umehara and colleagues recently reported that the membrane-associated receptor proteins Toll-like receptor (TLR) 7 and TLR8 can be used to separate mouse sperm cell fractions enriched either for X or Y chromosome-bearing sperm [1]. According to this study, Xencoded TLR7/8 are predominantly expressed in X-bearing sperm, and the activation of these receptors reduces sperm cell motility.…”
Section: Introductionmentioning
confidence: 99%
“…A gene that impedes its own reproductive success should be rapidly selected against and unable to persist in the population [2]. Below, we address various aspects of this mystery, focusing specifically on two key questions: (1) How are TLR7/8 specifically enriched in X-bearing sperm cells? And (2) what are the possible evolutionary consequences of this peculiar haploid selection mechanism?…”
Section: Introductionmentioning
confidence: 99%
“…In light of this finding, a number of cases of sperm-level functional differences in the literature can be putatively attributed to GIMs (Conway et al 1994; P. A. Martin-DeLeon et al 2005; Butler et al 2007; Véron et al 2009; Cocquet et al 2012; Alavioon et al 2017; Nadeau 2017; Umehara, Tsujita, and Shimada 2019). Despite the growing number of examples of sperm-mediated transmission ratio distortion, it has been widely assumed these are isolated cases and that mammalian sperm are functionally diploid as a rule.…”
Section: Discussionmentioning
confidence: 93%
“…In a mouse model for Niemann-Pick disease, heterozygous knockouts of Smpd1 have sperm with functional differences in mitochondrial membrane potential associated with their genotype (Butler et al 2007). Recently, TLR7/8 inhibitors have been reported to differentially affect sperm with the X or Y chromosome (Umehara, Tsujita, and Shimada 2019). Nevertheless, it is widely assumed that most gene products are shared between mammalian gametes, erasing any allelic expression bias.…”
Section: Introductionmentioning
confidence: 99%